Persepsi Followers Terhadap Gaya Hijab Turban Gita Savitri Pada Postingan Instagram @Gitasav - Rohidatun Nada; Ahmad Rofi’Syamsuri (Program Studi Komunikasi dan Penyiaran Islam, STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2025)
Gita Savitri is a Muslim hijab influencer whose turban-style hijab has generated both support and criticism. This controversy has been widely discussed on online platforms, particularly Instagram, as well as in offline communities, making it an interesting topic for academic research. This study aims to examine followers' perceptions of Gita Savitri's turban-style hijab as presented in her Instagram posts on the @gitasav account. To analyze this phenomenon, the researcher employed a descriptive qualitative approach. The study describes Instagram followers' perceptions through three stages of the perception process: sensation, attention, and interpretation. Data were collected through indepth interviews conducted by contacting participants directly via Instagram Direct Message (DM) and WhatsApp. The findings indicate that followers' perceptions of Gita Savitri's turban-style hijab on her Instagram posts can be understood through the three components of perception, namely sensation, attention, and interpretation.